Longer Nap Duration During Ramadan Observance Positively Impacts 5-m Shuttle Run Test Performance Performed in the Afternoon - Boukhris, Omar; Hill, David W.; Ammar, Achraf; Trabelsi, Khaled; Hsouna, Hsen; Abdessalem, Raouf; Mezghanni, Nourhen; Souissi, Nizar; Bragazzi, Nicola Luigi; Chamari, Karim; Chtourou, Hamdi (Frontiers in Physiology, 2022)
It is well-documented that changes in the rhythm of life during Ramadan affect sleep schedules (i.e., interruption of night sleep patterns) and are likely to have negative effects on physical and cognitive performances. The aim of the present study was to examine the effect of different naps opportunities’ durations during Ramadan on performance of short-duration repetitive maximal exercise and perception of effort. Fifteen physically active men (age: 21±3 years, height: 177±6 cm, body-mass: 73±10 kg) performed a 6×30-s shuttle run test after a 25-min nap (N25), a 45-min nap (N45), and in a no-nap condition (NN) during three experimental periods: ~2 weeks before Ramadan (BR), the last ten days of Ramadan (ER), and ~3 weeks after Ramadan (AR). During the shuttle run test performed in the late afternoon, the greatest distance (GD), the total distance (TD) and a fatigue index (FI) were assessed. Rating of perceived exertion (RPE) was determined after each 30-s effort. Dietary intake and sleep quality were assessed in each of the three periods. Compared to BR, GD and TD were lower in the ER testing period (p=0.005; d=0.54) but returned to BR levels in the AR period. During ER, carbohydrate intake was lower (p=0.04; d=0.2), and sleep duration and sleep quality were reduced (d=0.27 and 0.54, respectively), although other aspects of dietary intake and sleep pattern were not affected. Compared to NN, GD and TD were higher after N25 (d=0.57 and 0.34, respectively) and N45 (d=0.93 and 0.88 respectively). RPE was lower in N45 (p=0.035, d=0.84). N45 resulted in higher TD (p=0.021, d=0.13) and lower RPE (p=0.004; d=0.57) compared to N25 during ER. Taking a daytime nap benefits subsequent performance in a shuttle run test, whether sleep the previous night was normal (as in BR) or compromised (as in ER). The benefits of napping were greater after a 45-min nap opportunity than after a 25-min nap opportunity.